A study on the awareness and practice of modern and traditional methods for treatment of jaundice in an urban slum of Jorhat town, Assam - Dev, Anoop; Hazarika Medhi, Anuradha (International Journal Of Community Medicine And Public Health, 2019)
Background: Jaundice is a term use for the condition in which yellow colouration of the skin and the sclera occurs and is caused by a raised level of bilirubin. There are a number of herbal medicines or self-remedy medications widely in use among the people especially in the rural areas and suburbs. Various study showed that people have also switched over to modern methods of treatment. The purpose of the study is to assess the awareness of people towards Jaundice and the methods of treatment they preferred and practiced. Methods: The study was a community based cross-sectional study which was conducted amongst the people of an urban slum of Jorhat district of Assam, over a period of three months. A sample of 156 study participants of age group (21-60) was taken. Data were collected using a pre-designed and pre-tested proforma. MS excel and SPSS version-23were used to analyze the data. Results: Majority (88.4%) of the study participants were aware of Jaundice while amongst them (89.6%) respondents were in the age group of (21-30) years. (56.5%) study subjects were aware of traditional methods of treatment whereas only (5.1%) were aware of modern methods. However (36.9%) were aware of both traditional and modern methods. (74.6%) preferred as well as practiced traditional methods of treatment .Majority of respondents 56 (54.4%) had influence of society for practicing traditional methods for treatment of Jaundice followed by belief 32 (31.1%). Conclusions: Behaviour Change Communication (BCC) and Information Education Communication (IEC) activities regarding Jaundice should be promoted.